2019
DOI: 10.1002/jqs.3093
|View full text |Cite
|
Sign up to set email alerts
|

Environmental changes in the north‐east Sunda region over the last 40 000 years

Abstract: Pollen and spores from 110 samples from sediment core NS07‐25 from the Nansha Trough in the South China Sea (SCS) were analysed with a particular focus on reconstructing vegetation and climate change and identifying the sources of palynomorphs on the Sunda Shelf during the Last Glacial Maximum (LGM). Palynomorph sources were identified using the Near Analysis function in ArcGIS with 62 data points of the pollen in surface sediment samples from the southern SCS. The results showed that during the LGM, pollen an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…This finding may be due to the higher rainfall in the Holocene, which washed large amounts of terrestrial OM from the Borneo region, through the riverine pathway. In addition, the majority of pollen recorded in stage III was received from Borneo region through riverine pathways (Luo et al, 2019). Representing the higher abundance of C3 plants in the terrestrial OM, average δ 13 C org shows a smaller value of−24.01‰, and the signal of C3 plants is more prominent in δ 13 C org records during this stage (Figure 3).…”
Section: Climate Derived Terrestrial Paleo-vegetation Variationsmentioning
confidence: 95%
See 1 more Smart Citation
“…This finding may be due to the higher rainfall in the Holocene, which washed large amounts of terrestrial OM from the Borneo region, through the riverine pathway. In addition, the majority of pollen recorded in stage III was received from Borneo region through riverine pathways (Luo et al, 2019). Representing the higher abundance of C3 plants in the terrestrial OM, average δ 13 C org shows a smaller value of−24.01‰, and the signal of C3 plants is more prominent in δ 13 C org records during this stage (Figure 3).…”
Section: Climate Derived Terrestrial Paleo-vegetation Variationsmentioning
confidence: 95%
“…Aeolian fluxes from an arid land area/deserted area could trigger such a phenomenon with a low nutrient sediment input. When considering stage I, the pollen and spores may have been transported from northern Borneo area (around equator) (Luo et al, 2019) and as Aeolian flux, mainly from the mainland China.…”
Section: Climate Derived Terrestrial Paleo-vegetation Variationsmentioning
confidence: 99%
“…The primary objectives are to evaluate: (1) the influence of local sea-level rise on terrestrial deposition, (2) the response of mangrovederived sedimentary organic matter to MWP events, and (3) the deglacial evolution of mangrove ecosystem and implications on the carbon cycle and mangrove conservation. (Sun et al, 2002;Wang et al, 2009;Kumar et al, 2019a;Luo et al, 2019;Yang et al, 2020). The location of paleo-coastline at low sea level during the last glacial period was around the 120 m isobath (solid black line) (Hanebuth et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Mangroves growing near the shorelines in Southeast Asia account for the most significant proportion of mangrove forests globally (Thomas et al, 2017). However, their response to sea-level fluctuations, especially the global meltwater pulse (MWP) events during the last deglacial period, are not clear, although limited palynological studies have indicated vegetation dynamics and relatively high mangrove percentages during the last glaciation (Sun et al, 2002;Wang et al, 2009;Luo et al, 2019;Kumar et al, 2019b;Yang et al, 2020). Therefore, this study presents record of long-chain alkanes, long-chain alkanols, and taraxerol in sediments from the southern South China Sea to trace changes in the terrestrial input and mangrove carbon reservoirs during the last deglaciation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation